Statement and development of the Scientific library and departament of the scientific medical information of the acad. A.P. Romodanov Institute Neurosurgery AMS of Ukraine - Krichun, S. B.; Tretyak, I. B. (Ukrainian Neurosurgical Journal)
The short history of statement and development of scientific library and DSMI of the Institute of Neurosurgery named after acad. A.P. Romodanov AMS of Ukraine is presented. Also the librarian activity characteristic have been given since of the day of its foundation to nowadays. The activity of DSMI and scientific library is devoted to satisfaction of different inguires of scientifiс collaborators and doctors, introduction of new achievements into the practice of public health due to the subject and close contact nith the scientific department of the Institute.